Association of weight change and in‐hospital mortality in patients with repeated hospitalization for heart failure. Issue 1 (23rd December 2022) - Konishi, Masaaki; Kaneko, Hidehiro; Itoh, Hidetaka; Matsuoka, Satoshi; Okada, Akira; Kamiya, Kentaro; Sugimoto, Tadafumi; Fujiu, Katsuhito; Michihata, Nobuaki; Jo, Taisuke; Takeda, Norifumi; Morita, Hiroyuki; et al.
Abstract: Background: Although weight loss in heart failure (HF) is a detrimental condition known as cachexia, weight gain caused by fluid retention should also be considered harmful. However, studies with sufficient number of patients examining the impact of weight change and its interval on in‐hospital mortality in HF have not been conducted thus far. We sought to elucidate the association of weight change with in‐hospital mortality in patients with HF. Methods: This retrospective observational study used data from the Diagnosis Procedure Combination database, a nationwide inpatient health claims database in Japan. In total, 48 234 patients repeatedly hospitalized for HF (median 82 [74–87] years; 46.4% men) between 2010 and 2018 were included. Weight change was derived from body weight at the first and second admissions. Results: The median weight change and interval between two hospitalizations were −3.1 [−8.3 to −1.8] % and 172 [67–420] days, with 66.9% of overall cohort experiencing any weight loss. As a result of multivariable‐adjusted logistic regression analysis, weight loss <−5.0% and weight gain >+5.0% were associated with increased in‐hospital mortality (adjusted odds ratio [OR] [95% confidence interval]: 1.46 [1.31–1.62], P  < 0.001 and 1.23 [1.08–1.40], P  = 0.002, respectively) whereas mild weight loss and gain of 2.0–5.0% were not (OR [95% confidence interval]: 0.96 [0.84–1.10], P  = 0.57 and 1.07 [0.92–1.25], P  = 0.37, respectively), in comparison with patients with a stable weight (fluctuating no more than −2.0% to +2.0%) used as a reference. Restrictive cubic spline models adjusted for multiple background factors illustrated that higher mortality in patients with weight loss was observed across all subgroups of the baseline body mass index (<18.5, 18.5–24.9 and ≥25.0 kg/m 2 ). In patients with short (<90 days) and middle (<180 days) intervals between the two hospitalizations, both weight loss and weight gain were associated with high mortality, whereas the association between weight gain and high mortality was attenuated in those with longer intervals. Conclusions: Both weight loss and weight gain in patients with repeated hospitalization for HF were associated with high in‐hospital mortality, especially weight loss and short/middle‐term weight gain. Such patients should be treated with caution in a setting of repeated hospitalization for HF.